Where does the long 'journey' of the camels go? - Helena Bauer (Universitat Autonoma de Barcelona. Facultat de Dret, 2018)
Hardly any of us knows about the sad and appalling story of the camels in Egypt. Once being esteemed in the Bedouin culture as "the Bedouin's constant companion" the role of the camels in the Arab world has turned over the centuries. Nowadays they are mainly used for sports and leisure or as 'farm' animals bred and kept for milk and meat production. Egypt is one of the most important countries importing live camels. Every year hundreds of thousands of camels are imported as ‘slaughter’ animals particularly from Somalia and Sudan to provide the internal Egyptian market with camel meat. These transports by road, foot or sea are extremely long and exhausting for the camels, and some of them do not survive the exertions. At the markets they are faced with very rough and brutal handling methods. However, the alarming and wide-spread animal welfare problems generated from the unbearable transport and handling conditions which the camels must endure on transports, markets and in slaughterhouses in Egypt are not discussed up to the present day. Egypt is lacking any animal welfare legislation. Even though being member of the World Organisation of Animal Health (OIE), Egypt does not comply with the OIE standards on animal welfare in which also the camels are included. Therefore, it is high time to put an end to the extreme suffering of the camels and grant them the protection status they deserve.